Missing in Alaska : Hidden in the Night - Book 3 - Goddard, Elizabeth (Thorndike, Maine : Center Point Large Print, 2024)
"At the behest of her ailing mother, former FBI special agent turned rare-book collector Ivy Elliott arrives in Alaska to secure an unpublished Jack London manuscript kept secreted away for decades. But when she arrives, she learns the manuscript is gone -- taken by the granddaughter of the woman who possessed it. Ivy sets off in pursuit, not just to save the manuscript but to save the vulnerable girl, who was previously trafficked and has no idea what shes getting herself into. Joining forces with Alaska State Trooper Nolan Long, Ivy must battle a blizzard, sabotage, and the worst of an Alaskan winter as the search goes on. But every answer they find only raises more questions -- and the danger to their lives and to the missing girl may only be the tip of the iceberg."--
Keywords: Manuscripts -- Fiction; Missing persons -- Investigation; Fiction; Police -- Fiction; Rare books -- Fiction; Glacier Bay (Alaska) -- Fiction; Alaska -- Fiction; Detective and mystery fiction; Christian fiction; Thrillers (Fiction); Large print books